Delitev skupnega premoženja v zapuščinskem in pravdnem postopku - Končina Peternel, Mateja (Pravni letopis, 2013)
The division of the joint property of spouses and division of inheritance should be regulated in the similar way. The parties should retain the right to use the special rules of the procedure for the division of the joint property instead of the procedure of division of the separate thing in co-ownership. These special rules enable the parties to arrange their property relationship comprehensively.
Keywords: dedovanje; delitev; lastnina; marriage; premoženje; zakonska zveza